SALM1 controls synapse development by promoting F‐actin/PIP2‐dependent Neurexin clustering. (1st August 2019) - Brouwer, Marinka; Farzana, Fatima; Koopmans, Frank; Chen, Ning; Brunner, Jessie W; Oldani, Silvia; Li, Ka Wan; van Weering, Jan RT; Smit, August B; Toonen, Ruud F; Verhage, Matthijs
Abstract: Synapse development requires spatiotemporally regulated recruitment of synaptic proteins. In this study, we describe a novel presynaptic mechanism of cis ‐regulated oligomerization of adhesion molecules that controls synaptogenesis. We identified synaptic adhesion‐like molecule 1 (SALM1) as a constituent of the proposed presynaptic Munc18/CASK/Mint1/Lin7b organizer complex. SALM1 preferentially localized to presynaptic compartments of excitatory hippocampal neurons. SALM1 depletion in excitatory hippocampal primary neurons impaired Neurexin1β‐ and Neuroligin1‐mediated excitatory synaptogenesis and reduced synaptic vesicle clustering, synaptic transmission, and synaptic vesicle release. SALM1 promoted Neurexin1β clustering in an F‐actin‐ and PIP2‐dependent manner. Two basic residues in SALM1's juxtamembrane polybasic domain are essential for this clustering. Together, these data show that SALM1 is a presynaptic organizer of synapse development by promoting F‐actin/PIP2‐dependent clustering of Neurexin. Synopsis: This study shows that adhesion molecule SALM1 binds the presynaptic CASK/Mint1/Lin7b complex via its PDZ domain, while its juxtamembrane polybasic domain organizes synapse development by F‐actin/PIP2 dependent Neurexin clustering. SALM1 binds the CASK/Mint1/Lin7b complex and localizes to the presynaptic terminal. SALM1 depletion impairs Neurexin1β and Neuroligin1‐mediated synaptogenesis. SALM1 promotes F‐actin/PIP2 dependent Neurexin clustering via its polybasic domain. Acute SALM1 knockdown impairs synapse development and synaptic transmission. Abstract : The cell adhesion molecule SALM1 binds the presynaptic CASK/Mint1/Lin7b complex to promote neurexin clustering and synapse development.